Effect of interleukins on the proliferation and survival of B cell chronic lymphocytic leukaemia cells. Issue 5 (May 1995) - Mainou-Fowler, T; Copplestone, J A; Prentice, A G
Abstract : AIMS–To investigate the effects of interleukin (IL) 1, 2, 4, and 5 on the proliferation and survival of peripheral blood B cells from patients with B chronic lymphocytic leukaemia (B-CLL) and compare them with the effects on normal peripheral blood B cells. METHODS–The proliferation and survival of pokeweed mitogen (PWM) activated B cells from B-CLL (n = 12) and normal peripheral blood (n = 5) were studied in vitro in response to IL-1, IL-2 IL-4, and IL-5. Survival of cells in cultures with or without added interleukins was studied by microscopic examination of cells and DNA agarose gel electrophoresis. RESULTS–Proliferation was observed in both B-CLL and normal peripheral blood cells on culture with IL-2 alone and also in some, but not all, B-CLL and normal peripheral blood cells with IL-1 and IL-4. However, there was greater variability in B-CLL cell responses than in normal peripheral blood cells. Il-5 did not affect normal peripheral blood cell proliferation but it increased proliferation in two B-CLL cases. Synergistic effects of these cytokines were not detected. IL-4 inhibited normal peripheral blood and B-CLL cell proliferation after the addition of IL-2. Inhibition of B-CLL cell responses to IL-2 was also observed with IL-5 and Il-1. Survival of B-CLL cells in cultures was enhanced with IL-4 not by an increase in proliferation but by reduced apoptosis. No such effect was seen in normal peripheral blood cells. IL-2 had a less noticeable antiapoptotic effect; IL-5 enhanced apoptosis in B-CLL cells. CONCLUSIONS–B-CLL and normal peripheral blood cells proliferated equally well in response to IL-2. IL-4 had a much lower effect on B-CLL cell proliferation, but had noticeable antiapoptotic activity. IL-5 enhanced cell death by apoptosis.